Continuous quality improvement intervention for adolescent and young adult HIV testing services in Kenya improves HIV knowledge. (1st July 2017) - Wagner, Anjuli D.; Mugo, Cyrus; Bluemer-Miroite, Shay; Mutiti, Peter M.; Wamalwa, Dalton C.; Bukusi, David; Neary, Jillian; Njuguna, Irene N.; O'Malley, Gabrielle; John-Stewart, Grace C.; Slyker, Jennifer A.; Kohler, Pamela K.
Abstract : Objectives: To determine whether continuous quality improvement (CQI) improves quality of HIV testing services for adolescents and young adults (AYA). Design: CQI was introduced at two HIV testing settings: Youth Centre and Voluntary Counseling and Testing (VCT) Center, at a national referral hospital in Nairobi, Kenya. Methods: Primary outcomes were AYA satisfaction with HIV testing services, intent to return, and accurate HIV prevention and transmission knowledge. Healthcare worker (HCW) satisfaction assessed staff morale. T tests and interrupted time series analysis using Prais–Winsten regression and generalized estimating equations accounting for temporal trends and autocorrelation were conducted. Results: There were 172 AYA (Youth Centre = 109, VCT = 63) during 6 baseline weeks and 702 (Youth Centre = 454, VCT = 248) during 24 intervention weeks. CQI was associated with an immediate increase in the proportion of AYA with accurate knowledge of HIV transmission at Youth Centre: 18 vs. 63% [adjusted risk difference (aRD) 0.42, 95% confidence interval (CI) 0.21 to 0.63], and a trend at VCT: 38 vs. 72% (aRD 0.30, 95% CI −0.04 to 0.63). CQI was associated with an increase in the proportion of AYA with accurate HIV prevention knowledge in VCT: 46 vs. 61% (aRD 0.39, 95% CI 0.02–0.76), but not Youth Centre ( P = 0.759). In VCT, CQI showed a trend towards increased intent to retest (4.0 vs. 4.3; aRD 0.78, 95% CI −0.11 to 1.67), but not at Youth Centre ( P = 0.19). CQI was not associated with changes in AYA satisfaction, which was high during baseline and intervention at both clinics ( P = 0.384, P = 0.755). HCW satisfaction remained high during intervention and baseline ( P = 0.746). Conclusion: CQI improved AYA knowledge and did not negatively impact HCW satisfaction. Quality improvement interventions may be useful to improve adolescent-friendly service delivery.